La fabrique d’un patrimoine scolaire : la valorisation des œuvres du 1 % dans les lycées de Bourgogne - Guillaume Capou (In Situ)
The high schools of the Burgundy region possess a rich collection of 89 works acquired through the procedure of France’s legal provision called “1% artistique” (1% for Art) or “1% culturel” (1% for Culture). However, these works are little known to the staff and the students who walk past this local heritage every day. Acknowledging these works and integrating them into educational projects is the very challenge of their heritage enhancement.This article provides an analysis of the process of heritage enhancement and its issues. First, this will highlight the knowledge of these works by the actors in education, then, it will examine the tools developed and the scales involved in the enhancement of this heritage. Finally, a couple of more precise examples will allow us to review the processes and local issues of this heritage enhancement.These issues are related to artistic and cultural education development, but they also question the perception of educational institutions, namely the high schools. Indeed, at the core of the pedagogical enhancement of the works of the 1% for Art lies the challenge of an educational community identity, an elusive institutional object, and for which the 1% for Art could be meaningful.